Islamic Education Teacher Talent Management: A Competency Development Strategy in Islamic Junior Secondary Schools - Sucik Rahayu; Nur Izzati Ab Ghani (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2026)
Teacher competency development has become a significant challenge in Islamic education, particularly amid the demands of digital literacy and the improvement of learning quality. However, talent management practices for teachers in madrasahs have received limited contextual attention, especially regarding the integration of professional competencies with Islamic values. This study aims to analyze the implementation of teacher talent management in competency development at MTs Puteri Sunniyyah Selo. The research employed a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, and subsequently analyzed using the Miles and Huberman model. The findings reveal that teacher talent management is implemented through the identification of teachers’ potential, continuous competency development, the provision of non-financial rewards, as well as teacher placement and retention based on their competencies. This implementation is supported by leadership commitment and a collaborative work culture, although it still faces challenges in the form of limited facilities and the low utilization of digital technology in learning. The findings indicate that talent management contributes to improving teacher competencies and learning quality through the integration of professional, spiritual, and social dimensions. The novelty of this study lies in revealing talent management practices within the context of a female Islamic junior secondary school (madrasah) that integrates teacher professional development with the strengthening of Islamic values in a comprehensive manner.